Long-Term Clinical, Audiological, Visual, Neurocognitive and Behavioral Outcome in Children With Symptomatic and Asymptomatic Congenital Cytomegalovirus Infection Treated With Valganciclovir - Turriziani Colonna, Arianna; Buonsenso, Danilo; Pata, Davide; Salerno, Gilda; Chieffo, Daniela P. R.; Romeo, Domenico M.; Faccia, Valerio; Conti, Guido; Molle, Fernando; Baldascino, Antonio; De Waure, Chiara; Acampora, Anna; et al. (Frontiers in Medicine, 2020)
Background Cytomegalovirus (CMV) is the most common cause of congenital infection in humans. However, there are no enough data on long-term outcome of newborns with congenital CMV (cCMV) infection, particularly for those asymptomatic at birth. For this reason, we performed this study to evaluate long-term audiological, visual, neurocognitive and behavioral outcome in children with symptomatic and asymptomatic cCMV infection treated with oral Valganciclovir (VGC). Methods 8-year retrospective study of children with cCMV infection treated with oral valganciclovir. Children underwent audiological, visual, neurocognitive and behavioral follow-up. Results Study population: 36 newborns with confirmed cCMV infection were evaluated: 12 (33.3%) symptomatic at birth and 24 asymptomatic (66.7%). Avarage follow-up was 5.12 years. Cognitive development: 8/35 (22.8%) children scored below the norm. 3/35(8.5%) children achieved a borderline score. No one had cognitive impairment. Cognitive assessment scales resulted abnormal in 4/35 children (11.4%). Neuropsychological tests: 11/21 children (52.4%) achieved abnormal scores. The language evaluation gave pathological results in 6/21 (28.5%) children. Analysis of the child's behaviour: 7/28 (25%) children in total obtained alarming scores Audiological follow-up: 6/35 children (17.1%) developed SNHL, all symptomatic at birth except one Ophthalmological follow-up: None of the 34 children evaluateddeveloped CMV retinopathy. Conclusions Our study shows that both symptomatic and asymptomatic newborns with cCMV infection develop long-term sequelae, particularly in the behavioral and communicative areas, independently from the trimester of maternal infection.